Physiotherapy management of post-ORIF proximal femur with exercise therapy - Putri Karina Syafitri; Cicilia Febriani Hayuningrum; Galuh Jana Paramita; Dani Hafiz Utomo (Indonesian Journal of Health Science, 2026)
Background: Femur fracture is damage to the continuity of the femur bone which can be caused by direct trauma, muscle fatigue, or certain other conditions such as bone degeneration/osteoporosis. Objective: The ORIF technique is a surgical technique used to treat fractures by installing internal fixation in the form of plates and screws or nails. Method: This study employed a case study design involving a 56-year-old patient with post-ORIF proximal femur fracture. Exercise therapy was administered over six sessions within three weeks. Outcome measures included the Visual Analog Scale (VAS), goniometer, Manual Muscle Testing (M-MMT), anthropometric measurements, Berg Balance Scale (BBS), 30-second Chair Stand Test, Harris Hip Score (HHS), and Barthel Index. The results were a reduction in tenderness and movement pain, an increase in lower extremity muscle strength and joint range of motion in the right hip, increased balance, endurance, and increased hip functional ability. However, no changes were found in their daily independence. Conclusion: Exercise therapy given to patients with post-ORIF femur fractures can help reduce tenderness and movement pain, increase lower extremity muscle strength, increase dextra hip ROM, increase endurance, and increase hip functionality. However, there is little change in ADL abilities.